Max Plus at work : modeling and analysis of synchronized systems : a course on Max-Plus algebra and its applications - Heidergott, Bernd; Olsder, Geert Jan; Woude, J. W. van der (Princeton series in applied mathematics., 2006)
Trains pull into a railroad station and must wait for each other before leaving again in order to let passengers change trains. How do mathematicians then calculate a railroad timetable that accurately reflects their comings and goings? One approach is to use max-plus algebra, a framework used to model Discrete Event Systems, which are well suited to describe the ordering and timing of events. This is the first textbook on max-plus algebra, providing a concise and self-contained introduction to the topic. Applications of max-plus algebra abound in the world around us. Traffic systems, compu.